Psychometric Testing of the Technological Competency as Caring in Nursing Instrument – Revised (English Version Including a Practice Dimension) - Yokotani, Tomoya; Tanioka, Tetsuya; Betriana, Feni; Yasuhara, Yuko; Ito, Hirokazu; Soriano, Gil P.; Dino, Michael Joseph; Locsin, Rozzano C (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: The middle range theory Technological Competency as Caring in Nursing (TCCN) guides nursing practices. The TCCN Instrument (TCCNI) measures perception dimension of the theory and has been revised and translated into the Japanese language (TCCNI-R). Testing the translated version of the TCCNI-R to English language with the inclusion of a practice dimension is warranted.Purpose: This study aims to determine the psychometric properties of the TCCNI-Revised English version with Practice dimension (TCCNI-RePract).Methods: A web-based cross-sectional study was conducted with data from 202 valid questionnaire copies from professional nurses in selected hospitals and nurse educators in universities. Results: The suitability for factor analysis was determined using Kaiser-Meyer-Olkin index (0.93), Bartlett's sphericity test of 3256.93, p<0.001, the anti-image correlations ranged between 0.87 and 0.96, and an average value of communalities of 0.66. In the four rotations conducted with the maximum likelihood method with a Harris-Kaiser Orthoblique rotation, four items were excluded with factor loadings less than 0.40. These results determined the final scale with 21 items and four subscales, namely: (1) Knowing the person (8 items); (2) Technological competency as Caring (6 items); (3) Technology and caring (4 items); and (4) Expression of nursing as Caring (3 items). Cronbach’s alpha coefficient for the total scale was 0.94. With two dimensions of the TCCNI-RePract, the perception dimension had significantly higher scores than the practice dimension. When comparing mean factor point among the dimensions, the perception scores were significantly higher for Factor 1 and Factor 3.Conclusion:The TCCNI-RePract is an acceptable tool that can reliably measure nurses’ perception and practice of TCCN. It is affirmed that with this tool, measuring perception and practice status of TCCN theory is possible. It is considered that the evaluation results can be used to plan in-hospital education.